5α-Reductase inhibition and melanogenesis activity of sesamin from sesame seeds for hair cosmetics - Jiradej Manosroi (2018)
© 2015 Chiang Mai University. All rights reserved. Sesamin is the primary compound in sesame seed oil which has been used in ayurvedic treatment for hair loss and canities. Sesamin was isolated, identified and investigated for antioxidative activities (including DPPH radical scavenging, lipid peroxidation inhibition and metal ion chelating activities), 5α-reductase inhibition in DU-145 and melanogenesis activities on B16F10 melanoma. Sesamin at the concentration of 0.001-10 mg/ml showed weak DPPH scavenging activity (the SC50 value of 109.90 ± 6.16 mg/ml), but quite high lipid peroxidation inhibition and metal ion chelating activities (the IPC50 value of 0.83 ± 0.54 and the CC50 value of 1.83 ± 0.90 mg/ml, respectively). At 0.1 mg/ml of sesamin demonstrated high 5α-reductase inhibition activity at 37.38±4.26% of the control, which was higher than the standard finasteride of 1.54 times, but lower than the standard dutasteride of 1.27 times. It gave high melanin and tyrosinase contents of 26.63±3.21 and 39.42±8.30%, respectively, but lower than theophylline of about 1.04 and 1.05 times, respectively. Although sesamin exhibited all investigated activities lower than the standards, the traditional use of sesame seeds containing sesamin for hair cosmetics has been confirmed, which will be beneficial for the further development as anti-hair loss and anti-canities products.